Gurami mozaikowy dyryguje Beethovenem. Oniryczny panfikcjonalizm Scen łóżkowych Adama Wiedemanna - Lemann, Natalia (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The paper discusses musicality of Sceny łóżkowe (Bedtime scenes) by Adam Wiedemann understood as the constructive and topical dominant of the book. The writer`s ‘dream diary’ (including a ‘testimonio’ notation of dreams from 1987 to 2000), simulating the poetics of a personal document, in fact draws the reader into multilevel intertextual games. The consequent amalgamation of high and pop culture and the poetics of collage or sampling organize the dreams records of Sceny łóżkowe. The author analyzes Wiedemann`s work as a manifesto of panfictionalism and constructivistical ‘world making’ (cf. Siegfried J. Schmidt, Ernst von Glaserfeld, Steven Tötsöy de Zepetnek, Nelson Goodman). This in turn results in revealing the false referentialism or, more precisely autopoietic self-referentialism of Wiedemann`s writing, thus showing how unuseful traditional psychoanalisys and interpretation of dreams are for analyzing the manifestly constructivistical fabric of the writer’s humoristic and grotesque oneiric projections